Perilaku Menyimpang Anak Buruh Migran Indonesia di Desa Sidaharja Kabupaten Ciamis - Tresna Nurida; Rakhmat Hidayat (Indonesian Journal of Sociology, Education, and Development, 2023)
Indonesian women migrant workers are women workers who work abroad, working in the domestic sphere such as domestic servants. The majority of working women are married and have a husband and children, mothers work to meet the economic needs of the family. In this condition there is a mathematical between the role of women as a mother and wife and as the backbone of the family. There are several obstacles that occur due to mothers working abroad and being away from families, especially children, namely deviant behavior. The purpose of this study is to describe the deviant behavior of the children of Indonesian migrant workers in Sidaharja Village, Lakbok District, Ciamis Regency. In this study using a qualitative approach with descriptive methods, collecting data through observation, interviews and documentation studies. The results of his research include 1) the causes of migrant workers' children having deviant behavior, namely internal factors a) children feel lonely and lack of affection, b) children feel less attention from the family, especially mothers and c) children feel inferior because mothers work as migrant workers while external factors namely the community perspective on migrant workers' children; and social environment. 2) The form of deviant behavior is skipping school to dropping out of school,; wandering until late at night; and smoking and refuting parents. 3) Strategies for implementing character education in the family, which are to instill the values and norms that apply; and apply good parenting. 4) Solution of deviant behavior, namely the family as an agent in implementing character education in children, schools as a facilitator for children to apply the value of character education; and community leaders function to improve social control in children.